Marketing Communication Strategies of Cultural and Tourism Departments of Gunungk Kidul and Sleman Regencies: A Comparative Analysis - Resa Ayu (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
Yogyakarta Special Province has several attractive destinations for tourist. Bantul, Sleman, Kulon Progo, and Gunungkidul regencies have been developing many ways to attract tourists so they desire to come its regency own places. As long as we know, each regency has been working hard to promote and persuade tourists to visit some places that was offere But, in the fact, the result or the amount of tourists that visited each regency was different. Accroding data, the number of tourist who visit Sleman regency is more numerous than Gunungkidul regency. In 2010 for example, the number of tourist who visited Sleman regency reached 3,595,924. While Gunungkidul regency just reached 352 244 tourists at the same time. That why, this research was intended to find out the marketing communication strategies that conducted by Cultural and Tourist Department of Sleman and of Gunungkidul. At the least, this research was aimed to undertand how Sleman and Gunungkidul regencies developthe strategical marekting communication for increase and catch more tourist to visit Sleman and Gunungkidul. Data was obtained by interviews and observation as well as literatures analysis. And the result showed us that Cultural and Tourist Department of Gunungkidul was still not optimum doing marketing communication acitivites. It lack sufficient human resources who can develop creatively to attract tourists. While, Sleman regencies was more experience and could develop marketing communication more diverse.